SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169039-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small Molecule CO2 Thickeners for EOR and Fracturing

Abstract: The ideal carbon dioxide (CO 2 ) thickener would be an affordable, safe, water-insoluble additive that could dissolve in CO 2 at typical wellhead and reservoir conditions during CO 2 enhanced oil recovery (EOR) and elevate the viscosity of CO 2 to the same value as the oil. Further, the additive would not require heating or an organic co-solvent to achieve dissolution. A CO 2 thickener could be a transformative technology in that it would eliminate unfavorable mobility ratios during CO 2 EOR and reduce or elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…However, there was no significant increase in CO 2 viscosity under these conditions. This calls into question some of the results by Bullen and co-workers as they are much better than later literature [2].…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 78%
See 4 more Smart Citations
“…However, there was no significant increase in CO 2 viscosity under these conditions. This calls into question some of the results by Bullen and co-workers as they are much better than later literature [2].…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 78%
“…P-1-D and poly(vinyl ethyl ether) (PVEE)) ( Figure 1) could increase the viscosity of CO 2 by 13-14-fold at 329 K [15]. Previous research groups found that neither a 1 wt% mixture of PVEE nor P-1-D was capable of enhancing the viscosity in either toluene or CO 2 by more than several percents [2,6,8]. Therefore, Zhang et al findings do not correlate and are inconsistent with the results of other research groups.…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 96%
See 3 more Smart Citations